MORPHOLOGICAL CHANGES IN THE BONE TISSUE OF THE CHILD'S BODY IN THE AGE ASPECT - Palvanova M.S. (Scholar Express Journals, 2023)
It is known that the bone system, in addition to being a support that protects the body in a certain state, also participates in metabolism in the production of vitally necessary blood. It is important for family doctors to check the children's musculoskeletal system. Through this, doctors find solutions to issues such as early diagnosis of diseases, treatment of these diseases and prevention of disability among children.
Keywords: Ossification; epiphysis; Havers